Pengaruh Menghafal Al-Qur’an Terhadap Kecerdasan Spiritual Santri Al-Furqon Darul Ulum Peterongan Jombang - Maria Ulfa Yundiafi; Abd Kholid; Waslah Waslah (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
Today most people are only interested in world affairs, hence the need for religious education from an early age. Religious education in schools can also be improved through spiritual programs. Therefore, memorization of the Qur'an plays a very important role in increasing the spiritual intelligence of students. This research is an attempt to find out whether there is an effect of the Al-Qur’anmemorization program on the spiritual spiritual intelligence of the Santri Al-Furqon Dormitory Darul Ulum Peterongan Jombang students. This study uses quantitative methods with data processing methods with correlation analysis. The subjects of this research were the students of Al-Furqon Dormitory Darul Ulum Peterongan Jombang. With a sample of 30 students, this study used a questionnaire or questionnaire as a research tool to collect the required data or information. To complete the required data, this study also used observation, interview and documentation methods. Data analysis technique uses product moment. After analyzing the data using product time, taking into account the size of the product moment correlation test results rcount 0.404 > r table 0.361 This illustrates that the variable (x) memorizing the Koran with the variable (y) spiritual intelligence has a relationship. To find out the magnitude of the relationship between the 2 variables using the KD formula = r 2 x 100%. If r = 0.404 and r 2 = 0.163. So, the relationship between the variable x (memorizing the Qur'an) and the variable y (spiritual intelligence), namely 16.3% and 83.7%, can be influenced by other factors such as motivation, surrounding environment and others. So there is an effect of memorizing the Koran on spiritual intelligence of 16.3%